Alloy Nanoparticles for Hydrogen Sensing - levin, sune (My University, 2016)
Detecting hydrogen with nanoplasmonic sensing is a fairly new concept with the promising prospect of producing compact and precise hydrogen sensors with a low cost, due to the small amount of materials needed. In order to explore this possibility, material properties of various nanoparticle compositions should be examined to get a good understanding for these systems as well as finding the most suitable materials. In this master thesis project I have studied absorption and desorption of hydrogen in PdAu alloy nanoparticles to determine their thermodynamic and kinetic properties. This was done with direct nanoplasmonic sensing utilizing the change in LSPR (Localized Surface Plasmon Resonance) when changing the concentration of hydrogen in the nanoparticles. The main focus has been on determining the critical temperature TC for PdAu alloy nanoparticles with a concentration of gold ranging from 0 to 30 at%. Using two different methods, Van’t Hoff equation and data collapse, TC is found to decrease with increasing gold concentration. This decrease goes from 250 for pure palladium to below 100 for alloys with gold concentration greater than 15 at%. For gold concentrations of 20% and above, TC might already be below room temperature, but an unexpected hysteresis present at all hydrogen pressures was found, complicating the result interpretation. The reason behind this hysteresis is widely discussed in this report and the most likely explanation seems to be particle-substrate strain. Furthermore, the response time of the rate limiting step t90 for both hydrogen absorption and desorption is found to decrease with increased gold concentration. A quantitative decription of the energy landscape for hydrogen desorption was also derived by continuously analyzing change in the LSPR signal of the alloy particles during dehydrogenation
Keywords: Nanoteknik; Grundläggande vetenskaper; Hållbar utveckling; Innovation och entreprenörskap (nyttiggörande); Nanovetenskap och nanoteknik; Nano Technology; Basic Sciences; Sustainable Development; Innovation & Entrepreneurship; Nanoscience & Nanotechnology